ANALISIS KEBIJAKAN LUAR NEGERI ERA KEPEMIMPINAN KIM JONG UN DAN MOON JAE IN TERHADAP RESOLUSI KONFLIK SEMENANJUNG KOREA - Sofiyatul Khoiriyah (UIR Press, 2020)
Nuclear development in North Korea has become a worry and a threat to South Korea which has not been endless to date. Looking at the geographical, political and historical conditions of the two Korean Peninsula countries, it appears that South Korea will be threatened and harmed by the instability of North Korean behavior. The focus of this article is to analyze the foreign policy taken by the leaders of the two Korean Peninsula countries, Moon Jae In and Kim Jong Un, and the factors that led them to make that decision. Given the leader of a country is a state instrument that determines the geopolitical direction of the country. The author also wants to explain the history of the causes of the nuclear crisis in the Korean Peninsula country to the present point and the author wants to analyze the efforts that have been made as a nuclear and missile settlement mission in Korea and what solutions have been produced. The analysis used in this article is the rational actor model approach by Graham T Allison. This article focuses on changing the power used, namely hard power and soft power. In this article the authors take qualitative methods and secondary data collection techniques.